Bring Now the Angels : Poems - Ahmed, Dilruba (Pitt poetry series., 2020)
This collection juxtaposes text from Google Search autocomplete with the intimate language of prayer. Corporate jargon co-exists with the incantatory and ancient ghazal form. Ahmed's second book of poetry explores the terrain of loss--of a beloved family member, of human dignity & potential, of the earth as it stands, of hope. Her poems weave mourning with the erratic process of healing, skepticism with an unsteady attempt to regain faith. With poems that are by turns elegiac, biting, and tender, Bring Now the Angels conveys a desire to move toward transformation and rebirth, even among seemingly insurmountable obstacles: chronic disease, corporate greed, environmental harm, and a general atmosphere of anxiety and violence.